Desenvolvimento e aplicação de algoritmos adaptativos de busca tabu para a resolução de Problemas de Roteamento de Veículos Periódicos (PRVP) - Hallal, Renato (2004)
This research consists of the development of algorithms to solve the Periodic Vehicle Routing Problem (PVRP), wich has not received a great deal of attention in the O.R. literature. The objective of the PVRP is to elaborate a set of routes to attend to customers demand along a planning horizon. Each customer roquests that the visits occur in a combination predefined of days. Two heuristics were developed for the PVRP. In the first heuristic, three types of initial solution construction are used to attribute the customers to days. After that, visiting day combinations are changed in order to improvr the solution. The search process is controlled by an adaptative tabu heuristic from the literature which determines intensification and diversification actions, applied for each day in the period. The second heuristic incorporates a similar approach for the period as a whole. Computacional results show that this approach leads to good solution.